Numerical investigation of the concave-cut baffles effect in shell-and-tube heat exchanger (2019)
In this paper, the performance of shell-and-tube heat exchangers with single-segmental baffle and varying configurations of concave-cut baffles (10, 15 and 20 %) was investigated. The study was carried out for a heat exchanger having either engine oil, water and air as shell-side fluid. For each configuration of the baffles, the results of both the k-ε and RNG k-ε turbulent models were in very close agreement. The heat exchangers with concavecut baffles had higher pressure drops and lower performance factors than that of single-segmental baffle at the same range of mass flow rates for all fluid cases. Also, the concave-cut baffle heat exchangers had lower shell-side heat transfer coefficients at the same pressure drop against that of single-segmental baffles. Thus, the use of concave-cut baffles did not exhibit desirable performance in heat exchanger as compared with the segmental baffles.